2004
DOI: 10.1128/jvi.78.15.8281-8288.2004
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric Hantavirus Nucleocapsid Protein Binds Specifically to the Viral RNA Panhandle

Abstract: Hantaviruses are tripartite negative-sense RNA viruses and members of the Bunyaviridae family. The nucleocapsid (N) protein is encoded by the smallest of the three genome segments (S). N protein is the principal structural component of the viral capsid and is central to the hantavirus replication cycle. We examined intermolecular N-protein interaction and RNA binding by using bacterially expressed Sin Nombre virus N protein. N assembles into di-and trimeric forms. The mono-and dimeric forms exist transiently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 24 publications
4
92
1
Order By: Relevance
“…Separate or overlapping domains of N are likely to be involved in cap-recognition and panhandle recognition, required for cap-snatching/translation and genome encapsidation, respectively. The panhandle is recognized with specificity and high affinity by N. 69 As discussed in the text, N also binds to 5' caps of cellular mRNAs through its eIF4E-like activity. Cleavage of the bound cellular mRNA, presumably by the polymerase, generates a capped oligonucleotide.…”
Section: Role Of N In Translation and Cap-snatchingmentioning
confidence: 99%
“…Separate or overlapping domains of N are likely to be involved in cap-recognition and panhandle recognition, required for cap-snatching/translation and genome encapsidation, respectively. The panhandle is recognized with specificity and high affinity by N. 69 As discussed in the text, N also binds to 5' caps of cellular mRNAs through its eIF4E-like activity. Cleavage of the bound cellular mRNA, presumably by the polymerase, generates a capped oligonucleotide.…”
Section: Role Of N In Translation and Cap-snatchingmentioning
confidence: 99%
“…First, a T7 terminator was excised from pSNV N plasmid using NotI and SphI restriction sites and cloned between the same sites in a PUC19 vector to generate the pUCT7ter plasmid. Second, the gene encoding the viral S segment mRNA with appropriate 5Ј and 3Ј UTR sequences was PCR-amplified from pADS vector (27) using the forward primer (5Ј-ATTATATCCCGGGTAATACGACTCACTATA-GGAGTGAGTGTAGTAGTAGACTCCTTGAGAAGCTAC-TACGACTAAAG) and the reverse primer (5Ј-ATTATTAGC-GGCCGCCGTCTCATTATATACCCTGTAATATAATTG-GCCCTG). The forward primer with flanking T7 promoter contained the XmaI restriction site, and the reverse primer contained the NotI and BsmBI restrictions sites.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple in vitro studies have shown that N preferentially binds viral RNA compared with complementary RNA or nonviral RNA (14,(21)(22)(23)(24)(25)(26). It has been proposed that the specific binding of N with either the panhandle or the sequence at the 5Ј terminus alone selectively facilitates the encapsidation of viral RNA to generate three nucleocapsids that are packaged into infectious virions (26,27). The RNA binding domain of Hantaan virus N has been mapped to the central conserved region corresponding to amino acid residues 175-217(25).…”
mentioning
confidence: 99%
“…RNA Synthesis by T7 Transcription Reaction-DNA encoding the full-length S segment RNA molecule with a proximally located T7 promoter was generated by PCR using an upstream primer containing a T7 promoter sequence, a downstream primer that overlaps the terminal sequence of the S segment transcription unit, and a pAD-S plasmid as template, as described previously (26). The resulting DNA containing the entire S segment transcription unit was gel-purified and used directly in transcription reactions with T7 RNA polymerase (MBI Fermentase).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple in vitro studies have shown that N preferentially binds vRNA compared with complementary RNA (cRNA) or nonviral RNA (13, 20 -25). It has been proposed that the specific binding of N with either the panhandle or the sequence at the 5Ј terminus alone selectively facilitates the encapsidation of vRNA to generate three nucleocapsids that are packaged into infectious virions (25,26). The RNA-binding domain of Hantaan virus N protein has been mapped to the central conserved region corresponding to amino acids from 175 to 217 (24).…”
mentioning
confidence: 99%